CO Vigilance: Empowering Vehicle Safety with Health Alert Technology - Michael, Mary Vyonnie; Audrey Huong Kah Ching (Evolution in Electrical and Electronic Engineering, 2023)
The CO Vigilance: Empowering vehicle safety with health alert technology addresses the risk of carbon monoxide (CO) poisoning in non-moving vehicles by providing early warning and initial emergency reaction itself, empowering users to take immediate action and activate safety features, thus mitigating the potential dangers of CO exposure. The main objectives of this project are to design a portable CO detection device for in-car use, simulate fail-safe mechanisms for activating safety measures in response to high CO levels, and create a user-friendly interface for easy access to CO detection and safety controls, utilizing ESP32 microcontroller, with a scope that includes circuit design, prototype development, and integration with the Blynk IoT platform. The study utilized standard materials, methods, and procedures to ensure accurate and reliable data collection. Key findings revealed the effectiveness of the CO system, with real-time measurements displayed on an OLED screen and additional safety features such as alarms and automated window-opening mechanisms. The discussion highlights the successful reduction of CO exposure risks through the integration of IoT technology, user-friendly interfaces, and safety mechanisms. Future work suggestions include further optimization and refinement of the CO detection system to enhance its performance and expand its applicability.